RISK OF ASTHMA DUE TO THE EXISTENCE OF PSYCHOLOGICAL DISORDERS DURING PREGNANCY AND RISK OF ASTHMA IN CHILDREN - Nanda Agnesia Jati Pratiwi (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background: Asthma during pregnancy is a trigger factor for complications in pregnancy. Asthma is a chronic disease of the respiratory tract which can cause complications including the risk of asthma in the offspring, abortion, fetal death, and hypoxia. Psychological factors are often found to be the cause of asthma in pregnancy, such as stress which continues with anxiety and depression. In addition, asthma during the prenatal period is also associated with asthma in later babies. Objective: To understand of risk of asthma during pregnancy and their children after birth. Methods: This article will discuss a literature review by searching for journal articles on electronic media using the referencing period between January 2000 and January 2021. Results: Psychological disorders such as stress and anxiety are psychiatric conditions that are felt to be unpleasant and are associated with the causative factors for the onset of asthma or asthma recurrence and the management of asthma itself. The psychological disorder, either in the form of stress or anxiety, hurts the health condition of the mother during her pregnancy. The stress experienced by the mother during pregnancy also hurts her child in the future. This has pathophysiology, namely due to the continued secretion of cortisol as a result of axial activation in the hypothalamus and hypophysis glands which will eventually lead to T Helper 2 (Th2) cells in the fetus of birth. Conclusion: There is a correlation between the risk of asthma during pregnancy to their children after birth. Keywords: psychological disorders, stress, depression, pregnancy, asthma.